Branded! : how retailers engage consumers with social media and mobility - Brennan, Bernie (Wiley and SAS business series, 2010)
How retailers can create an effective strategy for using social media and mobility Written in a blog format to help retailers experience interactive dialog in this rapidly growing communication vehicle, this book will create awareness of social networ